The influence of trust and knowledge management on workers safety climate at ISAVIA's aerodromes : a case study - Hildur Baldvinsdóttir 1983- (2016)
The main purpose of this case study was to examine whether the employees’ perception of trust and knowledge management within ISAVIA’s aerodrome could positively influence their perception of workers safety climate. The theoretical background used for this analysis was based on Zohars recommendations that other variables influencing workers safety climate needed to be explored and how, by applying the theory of planned behaviour, a safety climate within an organization could positively influence safety behavior. Also it was examined which knowledge management practices were making the largest contribution to workers safety climate and finally detecting if the two aerodrome operations within ISAVIA differed on any of the variables. Data was collected from 106 aerodrome employees, 59 from Keflavík aerodrome and 47 from the domestic aerodromes. The main finding were that both trust and knowledge management do influence the workers safety climate with trust being the better predictor. Knowledge sharing was the only knowledge management practice that made a significant contribution in influencing workers safety climate when analyzed together with trust. Finally there was no significant difference between the two aerodrome operations KEF and DOM indicating that the operations have a similar perception of, workers safety climate, organizational trust and its knowledge management. The studies implications are that more focus should be on knowledge management regarding workers safety climate as it together with trust can serve as an antecedent for workers safety climate. Tilgangur þessa verkefnis var að skoða hvort upplifun starfsmanna innan flugvallarreksturs ISAVIA á trausti og þekkingarstjórnun hefðu áhrif á upplifun þeirra á öryggisanda. Sá kenningarlegi rammi sem stuðst var við byggðist bæði á tillögum Zohar (2010) að þörf væri á að skoða betur þá þætti sem geta haft áhrif á öryggisanda starfsmanna innan fyrirtækja og kenningunni um skipulagða hegðun, hvernig öryggisandi getur haft jákvæð áhrif á æskilega ...